2017
DOI: 10.1021/acs.jafc.7b03933
|View full text |Cite
|
Sign up to set email alerts
|

Rutinosylated Ferulic Acid Attenuates Food Allergic Response and Colitis by Upregulating Regulatory T Cells in Mouse Models

Abstract: The purpose of this study was to screen phytochemicals capable of inducing immune tolerance via enhanced transforming growth factor-β1 (TGF-β1) secretion and investigate their effects in a mouse model of food allergy and colitis. In a screening test using THP-1-derived dendritic cells, a significant increase in TGF-β1 levels was observed upon treatment with ferulic acid and its glycosides, among which ferulic acid rutinoside (FAR) induced the highest level of TGF-β1 secretion. Oral administration of FAR suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…For example, Cho et al found that sustained FA treatment of mice can suppress Aβ-induced astrocyte activation, thereby preventing the associated inflammatory cytokine and free radical production that can drive AD-associated inflammation [24]. FA treatment attenuated dextran-sulfate-sodium-induced colitis in the model mice and induced Treg differentiation [25]. FA can also suppress LPS-mediated IL-1β and IL-6 secretion from macrophages [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cho et al found that sustained FA treatment of mice can suppress Aβ-induced astrocyte activation, thereby preventing the associated inflammatory cytokine and free radical production that can drive AD-associated inflammation [24]. FA treatment attenuated dextran-sulfate-sodium-induced colitis in the model mice and induced Treg differentiation [25]. FA can also suppress LPS-mediated IL-1β and IL-6 secretion from macrophages [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cho et al found that sustained FA treatment of mice can suppress Aβ-induced astrocyte activation, thereby preventing the associated inflammatory cytokine and free radical production that can drive AD-associated inflammation [18]. FA treatment attenuated dextran-sulfate-sodium-induced colitis in the model mice and induced Treg differentiation [19]. FA can also suppress LPS-mediated IL-1β and IL-6 secretion from macrophages [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cho et al found that sustained FA treatment of mice can suppress Aβinduced astrocyte activation, thereby preventing the production of associated in ammatory cytokines and free radicals that can drive AD-associated in ammation [25]. FA treatment attenuates dextran sulfate sodium-induced colitis in model mice and induces Treg differentiation [26]. FA can also suppress LPSmediated IL-1β and IL-6 secretion from macrophages [27].…”
Section: Discussionmentioning
confidence: 99%